Q14 Sub maximal exercise testing in people with early stage Huntington's disease. (29th August 2012) - Jones, K; Jones, U; DeBono, K; Quinn, L; Dawes, H; Backx, K; Rosser, A; Busse, M; ,
Abstract : Background: Exercise is suggested to be of benefit to people with Huntington's disease (HD), however little is known about how they respond to exercise. This study investigated sub-maximal exercise testing in HD. Methods: Twenty subjects with HD (mean (SD) age 48.5 (10.2); total functional capacity (TFC) 8 (3) performed a sub-maximal cycle test with 3 min warm up (no load). Workload (watts) was increased from minutes 3 to 5 aiming for a target heart rate (HR) (80% of 220-age) in beats per minute (bpm). Validity of testing relies upon achieving steady state HR over minutes 7–9. Rating of perceived exertion (RPE) (Borg CR-10 scale) was recorded every minute. A group of age-matched healthy controls (mean age (SD) 51.5 (10.6)) completed the testing protocol to allow for normative comparisons using Mann–Whitney U tests. Results: Fifteen subjects with HD achieved steady state HR. Mean (SD) HR (HD 138 (16) bpm: control 135 (13) bpm; p=0.14), and RPE (HD 5.4 (2.3): control 4.4 (1.4); p=0.1) at steady state were not different. The mean (SD) workload at target HR (80% of 220-age) was significantly lower in HD (76 (45)) than in controls (102.3 (32.9)) (p=0.04). Conclusions: The majority of people with HD in this study successfully performed a sub-maximal fitness test, although target HR was achieved at a lower workload than that achieved in controls. Further research is required to understand factors limiting those who were not able to reach steady state and to identify possible reasons for reduced workload capacity in HD.